SIMULASI ROUTING PROTOKOL BERBASIS DISTANCE VECTOR MENGGUNAKAN GNS3 VERSI 0.8. - Ade Nurhayati; Adam Pangestu (Website, 2016)
Measurement of routing protocol performance in a network can be done with the help of simulation. The writers are trying to simulate package delivery data over Virtual Private Network (VPN) with the use of Graphical Network Simulator version 0.8.6 (GNS3). The topology used in the delivery of data packets is a ring topology which consists of 6 routers based on distance vector routing protocol. The results of simulation that the writers get are the throughput of the wireless and wireline on the server and client were averaging 1Mbit/s. The packet loss values generated for both wireless and wireline were 0 %. The measurement delay of the wireless and wireline for server and client side were averaging 7 ms.Pengukuran performansi routing protocol dalam suatu network dapat dilakukan dengan bantuan simulasi. Penulis mencoba mensimulasikan pengiriman paket data melalui Virtual Private Network (VPN) menggunakan simulator Graphical Network Simulator versi 0.8.6 (GNS3). Topologi yang penulis gunakan dalam pengiriman data paket menggunakan topologi ring yang terdiri dari 6 router, dengan salah satu routing protokol yang berbasis distance vector. Hasil simulasi yang penulis dapatkan nilai throughput dari wireless maupun wireline pada sisi server dan client rata-rata 1Mbit/sec. Sedangkan untuk nilai packet loss dihasilkan 0% baik itu wireless dan wireline dari posisi server ataupun client. Pengukuran pada delay wireless maupun wireline pada sisi server dan client rata-rata 7ms.